A method of maintaining healthy blood cholesterol levels and improvement of antioxidant status. - Azlan, Azrina; Ismail, Amin (2010)

(untitled)
The present invention discloses a vegetable fat/oil from Canarium odontophyllum pulp (COPO), a food article or food material that is excellent in maintaining healthy blood cholesterol levels and improvement of antioxidant status. More specifically, the present invention relates to a vegetable oil (COPO) that reduces plasma triglyceride (TG) and plasma low-density lipoprotein cholesterol (LDL-C) levels, and inhibits lipid peroxidation; increased plasma high-density lipoprotein cholesterol (HDL-C) level, and increased total antioxidant status; maintain plasma LDL/HDL cholesterol ratio in general.